Factores de pasantes en servicio social hospitalario que condicionan transitar hacia la conciencia activa - Ávila Cortés, Cynthia (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
Moving towards Consciousness Activa is to incorporate lessons learned in personal behavior, to make and remake based on reflective practice the way of change as the Maestro Julio Salgado Moya, this concept is adopted and adapted to nursing practice, interrelating the theoretical model Diversity and Universality of Madeleine Leininger, who explains that nursing care should be given to knowledge, science and humanism, which is evidenced by the joint use of taxonomy nurse and the nursing process. To achieve the transition to identify Active Consciousness is invited to participate in Hospital Nursing Interns Social Service, the latter being an academic process. METHOD. Joint Study sequential shunt. Quantitative phase: exploratory, observational and transversal. Qualitative phase: phenomenology. Study universe: all the interns were 22 for quantitative phase; a non-probability sampling was done for convenience qualitative phase. Data collection techniques: instrument (questionnaire) own design (? = .91) applied to the universe; semi-structured interview conducted with the sample were nine participants, a group discussion was conducted as approach to the issue between the stages of harvesting. RESULTS. 40.9% of the trainees have an age range from 22 to 25 years, 59.1% are academic graduates from technical level, home school graduates 59.1% are UMSNH. The expectations of the interns are the first evidence of transition to the active consciousness as 40.9% expected to learn new things and incorporate them in their professional life. Qualitative data show that 9 participants interviewed expressed that "move towards active consciousness is a personal decision" and what can influence for this are hospital nurses, school teachers, family and previous experiences.

Transitar hacia la Conciencia Activa es incorporar lo aprendido en el comportamiento personal, para hacer y rehacer con base en la práctica reflexiva el camino del cambio según el Maestro Julio Salgado Moya, éste concepto se adopta y adapta a la práctica enfermera, interrelacionándose al Modelo teórico de la Diversidad y Universalidad de Madeleine Leininger, quién explica que el cuidado enfermero debe darse con conocimiento, ciencia y humanismo, los cuáles, se evidencian con el uso conjunto de la taxonomía enfermera y el proceso enfermero. Para lograr identificar él Tránsito Hacia la Conciencia Activa se invitó a participar a Pasantes de Enfermería en Servicio Social Hospitalario, por ser éste último un proceso académico. MÉTODO. Estudio mixto secuencial por derivación. Fase Cuantitativa: exploratorio, observacional y transversal. Fase Cualitativa: fenomenología. Universo de estudio: la totalidad de las pasantes fueron 22 para la fase cuantitativa; se realizó un muestreo no probabilístico por conveniencia para la fase cualitativa. Técnicas de recolección de datos: instrumento (cuestionario) de diseño propio (α=.91) aplicado al universo; entrevista semiestructurada realizada con la muestra que fueron 9 participantes, se efectuó un grupo de discusión como aproximación al tema entre las etapas de recolección. RESULTADOS. 40.9% de las pasantes tienen un rango de edad de 22 a 25 años, en nivel académico 59.1% son egresadas del nivel técnico, por escuela de origen 59.1% son egresadas de la UMSNH. Las expectativas de las pasantes son una primera evidencia de transitar hacia la conciencia activa pues 40.9% esperaba aprender cosas nuevas e incorporarlas en su vida profesional. Los datos cualitativos muestran que las 9 participantes entrevistadas expresaron que “transitar hacia la conciencia activa es una decisión personal” y lo que puede influir para ello son las enfermeras del hospital, la escuela, sus maestros, la familia y las experiencias previas.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2016-1593; Conciencia activa; Servicio social; Pasantes de enfermería; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5629